NURSE EFFORTS IN THE PREVENTION OF ULCER PRESSURE IN MARDI WALUYO HOSPITAL, BLITAR CITY: UPAYA PERAWAT DALAM PENCEGAHAN PRESSURE ULCER DI RSUD MARDI WALUYO KOTA BLITAR - -, Sunarti -; Diah, Saputri (Bali Medika Jurnal, 2019)
Pressure ulcers (decuitus) are usually found in people who are treated in bed or have decreased mobility, especially if accompanied by poor nutritional status. The purpose of this study was to determine the picture of Nurses’ Efforts in Preventing Pressure Ulcers at Mardi Waluyo District Hospital in Blitar City. This research uses descriptive research design. The population of this study was 54 nurses in Melati room, Mawar room, and Bougenvile room Mardi Waluyo Regional Hospital in Blitar City using total sampling technique. Data collection was done by giving questionnaires. When the data was collected on June 8-30, 2016. The results showed that the efforts of nurses 70.4% (38 nurses) were sufficient. Based on parameters, 72.2% (39 nurses) are adequate, hygiene care and topical skin care, mechanical prevention and support tools 87.0% (47 nurses) are sufficient, health education 96.3% (52 nurses) is good. Recommendations in this study, nurses are expected to continue training in the prevention of pressure sores, and use guidebooks such as SOPs in carrying out every action of nursing care.